IMPLEMENTASI TEKNIK IMPROVISASI BERBASIS KEARIFAN LOKAL UNTUK MENINGKATKAN EKSPRESI DIRI SISWA TEATER DI SMPK SWASTA JAKARTA - Petrisia Sabattani; Jaeni; Yahfenel Evi Fuhsalam (CV. ADIBA AISHA AMIRA, 2025)
Contemporary formal theatre arts education tends to focus on conventional techniques and rigid scripts, which significantly limit students' exploration, creativity, and spontaneity at the secondary school level. Consequently, students' self-confidence and self-expression are often sub-optimally developed. This study aims to develop and validate structured improvisation techniques within the theatre arts curriculum to enhance students' self-expression, employing a Research and Development (R&D) approach with a case study location at a private Christian Junior High School (SMPK Swasta) in Jakarta. Qualitative methods, including participatory observation and in-depth interviews, were utilized, with data analysis conducted through the Miles & Huberman model. The intervention focused on the